A Chairpersons Guide to Managing Time and Stress - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2023)
In this interactive workshop we discuss time and stress management specifically from the perspective of a department chairperson responsible for leading an academic department through numerous internal and external challenges. The focus will be on practical strategies for effective use of time, not only at a personal level, but also at a department wide level.
Keywords: Time Management; Stress Management; Effectiveness; Leadership; Meeting Goals